Modernization of Ticketing System Using Re-Engineering Approach - Nik Ahmad, Nik Azlina; Hamzah, Muhammad Feezi (Journal of Computing Technologies and Creative Content, 2020)
Ticketing system is an enormous sector in Malaysia and other countries. Its range of use is applicable to both products and services. The manual ticketing system is tedious with time consuming when the consumers need to wait in a long queue. Due to this reason, a modernization to a legacy ticketing system is proposed in this paper to overcome such problems and to support the growing business operations and technology with the use of re-engineering approach. Constant demands for mobile applications and relatively easy access to the market have been drawing researchers into mobile application development. With this new replacement, it is trusted to improve the whole business processes and increase its usability, thus becomes the solution amongst indigenes within the country. A new system architecture as well as modernization and functional models were proposed and the usability of the prototype was evaluated using two different testing methods.